Improved Calculation Method for Shear Stress Nonuniformity Coefficient of Thin-Walled Flat Box Sections - Lihua Ling; Changsong Chen; Jin Wang; Donghuang Yan (Advances in Civil Engineering)
Based on the shear flow theory for thin-walled sections, a method for calculating the shear stress nonuniformity coefficient (µ) of a thin-walled section is proposed according to the energy principle, and the formulas for calculating the µ values of several common sections are derived. The obtained µ value of a box section increases as the aspect ratio increases. Compared with commonly used calculation methods, the proposed method gives more reasonable results and shows that the effect of shear stress in the flange of the flat box section should not be ignored. The effects of the web and flange thicknesses on µ are analyzed and discussed. Based on these effects, a simplified method for calculating the µ value of complex box sections is presented, and this method is demonstrated to considerably reduce the calculation error and meet engineering needs.